Pengaruh Aset Dan Modal Sendiri Terhadap Sisa Hasil Usaha (SHU) Pada Koperasi Simpan Pinjam Suru Pudi Koting - Yuliana Novita; Henrikus Herdi; Antonius Philipus Kurniawan (BADAN PENERBIT STIEPARI PRESS, 2023)
This research aimed to determine the effect of assets and own capital on the remining results of operations at the Suru Pudi Koting Credit Union. This research method was quantitative. The population in this research was the financial statements of the Suru Pudi Koting Credit Union and the sample used was the profit and loss statement of the Suru Pudi Koting Credit Union. Data analysis used multiple linear regression analysis. Hypotesis testing used a partial test (t-test), simultaneous test ( F-test), and determination coefficient test (R-test). The result of the research based on the t-test showed that partially or significantly the asset variable did not affect the remaining results of operations, own capital could affect the remaining results of operations, and the statistical results of the F-test showed that simultaneously all independent variables had no significant effect on the remaining results of operations